A Band-Rejection Vivaldi Antenna with High Selectivity Using Hybrid HRW/CCLL. (23rd April 2020) - Xiong, Mengfei; Duan, Junping; Zhang, Binzhen
Abstract : A simplified notched design method for the Vivaldi antenna is exhibiting high frequency-band-selectivity characteristics. By suitably introducing half-wavelength resonator (HWR) and complementary capacitively loaded loop (CCLL), the notched-band selectivity is promoted while maintaining the wide impedance bandwidth of the antenna applicable for wireless communications. HWR is bent in the middle to focus the first notch pole, and the second notch pole is obtained by CCLL on the radiating patch. Additionally, the resonant frequency of the notched pole can be determined by the position and size of two loaded resonators in theoretical analysis, thereby realizing a wideband antenna with the desired notched band. Finally, the Vivaldi antenna of loading resonator was fabricated to verify the feasibility of this new method. Measured and simulated experimental results reveal that the antenna exhibits directional pattern in the passband, low gain at the band-rejection, and excellent selectivity within a frequency range. The simulation and measurement results are in good agreement. The proposed antenna achieves S11<−10 dB in 2.6–13.7 GHz and a notch band from 4.49 to 6.64 GHz to reject IEEE 802.11a and HIPERLAN/2 frequency band. Moreover, the proposed antenna has good frequency selectivity, and its gain is good enough in the passband with peak gain up to 10.8 dBi. This antenna design presents frequency suitability, demonstrating that a UWB antenna with a controllable notched band has been realized.